Peran legalitas NIB terhadap efektivitas operasional dan akses fasilitas pemerintah pada UMKM Desa Samirono - Aula, Khakimah Himatul; Maulida, Dewi; Purwaningrum, Devvy Ayu; Mukaromah, Azizatul (Nur Science Institute, 2025)
The legitimacy and access to government support for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia are often hindered by the lack of business legality, particularly in rural areas like Samirono Village, where many MSMEs operate without formal documents such as the Business Identification Number (NIB), impacting their competitiveness and economic sustainability. This study aims to analyze the role of NIB legality in enhancing operational effectiveness and facilitating MSMEs' access to government facilities and programs in Samirono Village. A qualitative approach was employed using a descriptive participatory method, where MSMEs actively participated in the data collection process, packaged as a Work Program during the KKN KSEI UIN Salatiga 2025 activity, including coordination with village authorities, MSME data collection, and technical assistance for NIB registration. The results show that four MSMEs previously without NIB successfully obtained it through guidance, thereby increasing legal awareness, streamlining bureaucratic processes, and opening opportunities such as halal certification and capital access. So, NIB legality plays a crucial role as an empowerment strategy for MSMEs to achieve more effective operations and broader access to government support, with recommendations for the government to simplify licensing processes to support sustainable MSME development (conclusion).